ADVANCE CARE PLANNING FOR DEMENTIA PATIENTS. Issue 2 (1st June 2013) - McGee, Andrew
Abstract : Background: There is currently some debate about the extent to which advance decisions, advance statements of wishes and preferences, or other forms of advanced care planning should be followed when they are undertaken by a patient who subsequently loses capacity. Two main arguments commonly advanced to support the claim that these forms of advanced planning are problematic are: (a) the person who loses capacity is not the same person as the one who had capacity; and (b) the person retains certain autonomy in addition to welfare interests and so cannot be bound by priorly taken decisions or expressed wishes. Aim: This paper re-examines these two main arguments in the context of dementia patients. It rejects the first argument. However, it argues that the second argument is important and is often correct. Its correctness can only be determined in a case by case basis, taking into account all relevant circumstances. Nonetheless, this has implications for how we ought to draw up an advance decision that is to be legally binding, and for whether we ought to consider alternative forms of advance care planning. One alternative put forward in the Nuffield Dementia Report 2009 is a form of proxy decision making. This paper examines that proposal. Methods: Conceptual analysis of arguments (a) and (b), with some reference to the relevance of a recent English case to advance statements of wishes and preferences. Results: The paper concludes that argument (a) can be rejected, but that argument (b) is sound and has implications for the forms of advance care planning we ought to adopt in the case of dementia patients, and for the shape that current advance decisions now take. Discussion: A form of proxy decision making might be the best way of resolving the dilemma about how to respect autonomy and welfare interests that survive the loss of capacity in dementia patients. Conclusion: The form of proxy decision making proposed in the Nuffield Dementia Report 2009 is the best way of solving the dilemma and might be preferable to legally binding advance decisions.